Right to be Forgotten as a Legal Protection for The Victims of Electronic Sexual Violence Cases - Zaltina, Putri; Nurtjahyo, Lidwina Inge (UI Scholars Hub, 2024)
The 2020 National Commission on Violence Against Women's Annual Records identified the rise of a new type of violence against gender in Indonesia, specifically electronic-based sexual violence (Kekerasan Seksual Berbasis Elektronik/KSBE) which is part of gender-based violence in the digital spaces or Online Gender-Based Violence (OGBV). In 2020, KSBE cases increased 300% compared to the previous year. So far, the arrangements for tackling KSBE perpetrators in Indonesia have been inadequate. Existing laws do not contain procedures that are sensitive to victims and lack a human rights and gender perspective. Currently, Indonesia has adopted a new regulation related to handling sexual violence, namely Law No. 12 of 2022 on Sexual Violence Crimes. The authors analyse laws and regulations relevant to online sexual violence and its extension (involving physical action), from the perspective of human rights and women's rights. Thus, several significant regulations apart from the Sexual Violence Crimes Law are discussed, namely the Criminal Code, the Information and Transaction Law, the Anti-Pornography Law, and the Child Protection Law. We argue that protection of KSBE victims must be made the main goal of law enforcement. The loss of the victim's privacy and the dissemination of personal data violate victims’ human rights guaranteed by the state, and therefore derivative regulations regarding the UU TPKS (Sexual Violence Law) need to be issued and existing laws harmonized with it. Moreover, additional special victim rights regulations regarding electronic-based sexual violence are necessary, especially for KSBE acts that require a quick response, such as removing sexually explicit content.